2020
DOI: 10.3389/fpubh.2020.00374
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Contamination and Occupational Exposure of Algerian Hospital Workers

Abstract: Guidelines are in place to assure limited occupational exposure to cytostatic drugs. Even though this has led to a reduction in exposure, several studies reported quantifiable concentrations of these compounds in healthcare workers. In this study, we evaluated occupational exposure to cytostatic drugs in hospital workers from the University Hospital in Tlemcen, Algeria. Monitoring was performed by collecting wipe samples from surfaces, objects, personal protective equipment (gloves and masks) and from the skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 39 publications
0
6
0
3
Order By: Relevance
“…Despite these safety guidelines, the studies carried out over the recent years still have reported a residual contamination with antineoplastic drugs on surfaces and on the hands of hospital employees, including pharmaceutical workers. 610 Since the dermal route is considered as the major contamination pathway, these data reinforce the relevance of conducting further studies on occupational AD contamination, preferably with direct methods to detect traces of antineoplastic drugs or of their metabolites in healthcare workers. 5 , 11 , 12 These methods are essential in order to measure workers’ effective uptake of AD in the healthcare environment.…”
Section: Introductionmentioning
confidence: 74%
“…Despite these safety guidelines, the studies carried out over the recent years still have reported a residual contamination with antineoplastic drugs on surfaces and on the hands of hospital employees, including pharmaceutical workers. 610 Since the dermal route is considered as the major contamination pathway, these data reinforce the relevance of conducting further studies on occupational AD contamination, preferably with direct methods to detect traces of antineoplastic drugs or of their metabolites in healthcare workers. 5 , 11 , 12 These methods are essential in order to measure workers’ effective uptake of AD in the healthcare environment.…”
Section: Introductionmentioning
confidence: 74%
“…Nevertheless, ESI was the selected ionization source employed in the developed methods, as mentioned previously, due to the absence of signal for some compounds by US. To our knowledge, only one article has been published using US for the determination of 5-fluorouracil in wipe samples ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…Yang sering menjadi perhatian adalah petugas kesehatan yang terlibat selama persiapan dan pemberian obat. Paparan dapat terjadi melalui kontak dengan permukaan kerja yang terkontaminasi, peralatan, kotoran/ekskresi pasien, atau secara inhalasi dengan menghirup partikel yang dihasilkan akibat melakukan manipulasi terhadap larutan yang mengandung agen sitostatik tersebut (Verscheure et al, 2020).…”
Section: Pendahuluanunclassified
“…Sisasisa obat tersebut mungkin menimbulkan efek jangka panjang pada keluarga saat beraktivitas dengan pasien seperti membersihkan pasien, menggunakan toilet yang sama dan mengganti alas kasur yang terkontaminasi oleh urin, feses, muntah atau keringat pasien tanpa menggunakan alat pelindung diri (Hon et al, 2014). Efek tersebut dapat berupa efek mutagenik, perkembangan, reproduksi ataupun efek sitogenik (Verscheure et al, 2020).…”
Section: Pendahuluanunclassified
See 1 more Smart Citation